Common variation at the adiponectin locus is not associated with colorectal cancer risk in the UK. - Carvajal-Carmona, L; Spain, S; Kerr, D; Houlston, R; Cazier, J; Tomlinson, I (2009)
A recent study examined common genetic variants at the adiponectin locus (ADIPOQ) in two case-control colorectal cancer (CRC) series from the USA and reported a positive association between a single nucleotide polymorphism (SNP) in the 5' region of the gene (rs266729) and decreased disease risk. In an attempt to replicate the previously reported association, we examined data from two CRC genome-wide association studies based on the UK population. The first cohort comprised 931 familial colorectal tumour cases and 929 cancer-free controls. The second included 1216 individuals with Dukes stage B or C CRCs from two clinical trials and 1436 controls from the 1958 Birth Cohort. We tested associations between CRC risk and 82 SNPs in a region of 250 kb around the ADIPOQ gene; nine of these SNPs were located in the coding and promoter regions. None of the markers tested was significantly associated with CRC risk after correction for multiple testing under any of the models in any of the two cohorts. A meta-analysis of the data also failed to detect any association. We, therefore, failed to replicate an association between common variants at ADIPOQ and CRC risk in the UK, and suggest that the previous report is either population-specific or a false-positive result.